Analysis of Humoral Immune Responses in Patients With Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (31st October 2020) - Henss, Lisa; Scholz, Tatjana; von Rhein, Christine; Wieters, Imke; Borgans, Frauke; Eberhardt, Fabian J; Zacharowski, Kai; Ciesek, Sandra; Rohde, Gernot; Vehreschild, Maria; Stephan, Christoph; Wolf, Timo; et al.
Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has caused a pandemic with tens of millions of cases and hundreds of thousands of deaths. The infection causes coronavirus disease 2019 (COVID-19), a disease of the respiratory system of divergent severity. In the current study, humoral immune responses were characterized in a cohort of 143 patients with COVID-19 from the University Hospital Frankfurt am Main, Germany. Methods: SARS-CoV-2-specific–antibodies were detected by enzyme-linked immunosorbent assay (ELISA). SARS-CoV-2 and human coronavirus NL63 neutralization activity was analyzed with pseudotyped lentiviral vectors. Results: The severity of COVID-19 increased with age, and male patients encountered more serious symptoms than female patients. Disease severity was correlated with the amount of SARS-CoV-2–specific immunoglobulin (Ig) G and IgA and the neutralization activity of the antibodies. The amount of SARS-CoV-2–specific IgG antibodies decreased with time after polymerase chain reaction conformation of the infection, and antibodies directed against the nucleoprotein waned faster than spike protein-directed antibodies. In contrast, for the common flu coronavirus NL63, COVID-19 disease severity seemed to be correlated with low NL63-neutralizing activities, suggesting the possibility of cross-reactive protection. Conclusion: The results describe the humoral immune responses against SARS-CoV-2 and might aid the identification of correlates of protection needed for vaccine development. Abstract : Humoral immune responses in 143 German patients with coronavirus disease 2019 were analyzed. Disease severity was correlated with the amount and neutralization activity of severe acute respiratory syndrome coronavirus 2–specific antibodies. Compared with those with mild-moderate disease, patients with severe disease had only weakly neutralizing antibodies against coronavirus NL63.